Sign Language Research, Uses and Practices. Crossing Views on Theoretical and Applied Sign Language Linguistics - Meurant, Laurence (Sign Languages and Deaf Communities [SLDC], 2013)
The uses and practices of sign languages are strongly related to scientific research on sign languages and vice versa. Conversely, sign linguistics cannot be separated from Deaf community practices, including practices in education and interpretation. Therefore, the current volume brings together work on sign language interpreting, the use of spoken and sign language with deaf children with cochlear implants and early language development in children exposed to both a spoken and sign language, and reports on recent research on aspects of sign language structure. It also includes papers addressing methodological issues in sign language research. The book presents papers by more seasoned researchers and new kids on the block, as well as papers in which the two collaborate. The contributions will be of interest to all those interested in linguistics, sociolinguistics, cultural studies, interpreting and education. It will have particular relevance to those interested in sign linguistics, sociolinguistics of deaf communities, Deaf studies, Deaf culture, sign language interpretation, sign language teaching, and (spoken/signed) bilingualism. Given the scarcity of literature on Deaf studies, the book will also appeal widely beyond the traditional academic milieu. As a result, it has relevance for those teaching and learning sign languages, for professional and student interpreters and for teachers of the deaf.